Service Quality And Brand Image On Customer Loyalty At Grab-Bike Companies In Bandung City - Daniel Exaudi Christia; Ayuningtyas Yuli Hapsari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
ABSTRACT Due to the growth of several service-related firms, particularly online transportation, businesses in this sector are now competing for the public's favor by providing high-quality services and building strong brands. Grab is one of the online transportation firms that focuses service quality and has one of the largest user bases in Indonesia, which shows that the company's brand image is strong. Based on this, this study seeks to determine how customer loyalty to Grab transportation services is influenced by service quality and brand perception. An associative quantitative approach was used for the research, and a total of 75 Grab users were included in the sample through the Google form. Multiple linear regression analysis is the method used for data analysis, and a partial test (t-test) and simultaneous test are also used (F-test). And the findings demonstrate that customer loyalty is influenced by service quality and brand perception. Keywords : Service Quality, Brand Image, Customer Loyalty